PENERAPAN SPANNING TREE PROTOCOL TERHADAPWIDE AREA NETWORK (WAN) PADA PT. DUTA LESTARI SENTRATAMA JAKARTA - Achmad Wira Wiguna; Herlawati Herlawati; Budi Santoso (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2013)
With each passing year the development of technology and communication becoming increasingly advanced, especially computer equipment today is very fast development. In this day and age when we want to move forward, we are in demand to be able to master the variety of the many evolving technologies, especially computers that are currently widely used in industry and in the business world. PT. Duta Lestari Sentratama is companies that work day-to-day activities are very dependent on computer networks and data communications, and therefore knowledge of the constituent components of computer networks and software that is used in the form of data communication is very important to learn to achieve the needs of the principal. The purpose of writing this thesis is to describe and explain the form of computer network that is used in the PT. Duta Lestari Sentratama., And provide a network of proposals that would be better than the current network. Spanning Tree Protocol is a protocol that is networking switch that allows all devices to communicate with each other in order to detect and manage redundant link in the network, Spanning Tree Protocol can overcome a broadcast storm, in other words, the Spanning Tree Protocol to prevent repetitive data transmission the same package, so the user is not a lot of existing broadcast process.